The customary marriage and the issue of proving it: A comparative study - Recioui, Messaouda (The International tax journal, 2025)
Some believe that Customary Marriage may be a Solution to some of the Problems Facing Young People. Others; However; Believe that this Type of Marriage Leads to Several Social, Humanitarian, and Psychological Problems. Therefore; The Personal Status Laws in Arab and Islamic Countries, including the Algerian Family Law, Stipulate the Necessity of Registering Marriage Contracts and Recording them in the Civil Status Registers and Official Departments, for Practical Purposes that Protect Rights from being Lost. However; Some Individuals overlook this Procedure and Enter into Customary Informal Marriages without Registering them. This is a Social Phenomenon that is Increasing Day by Day, raising Legal and Practical Problems regarding the Issue of Proving such Marriages.